Management lessons from Italy: a bibliometric analysis of top Italian based scholars and studies published from 1985 to 2015. (2017) - Marzi, Giacomo; Caputo, Andrea; Dabić, Marina
Based on three decades of data collected via web of science (WOS) database, this paper offers a comprehensive overview of Italian managerial studies published in international journals indexed in the WOS core collection. This paper, taking in consideration 1, 665 researches made by Italian scholars or based in the Italian context, firstly shows the most influential papers, authors, and the most relevant journals. Furthermore, using keywords co-occurrences analysis, the paper shows the most relevant topics, how they are clustered together, and the relative importance in terms of number of citations. Finally, it provides a representation of keywords average novelty highlighting the past, the present, and the future trends in Italian managerial studies.